Police Power for Investigation Use and Misuse: CRPC References: Examining the Role of Police in Crime Prevention and Law Enforcement (Journal of Advances and Scholarly Researches in Allied Education, 2018)
“The police officer is an instrument for the prevention and detection of crime’’1Police play a key role in fighting crime, preserving peace, maintaining public order. They basically play a dual role while maintaining the law and order of any state. The head of the provincial police department is the Director-General of the police and in all provinces take the Legislature-The Police Officer.